The Development of Intensive Care Unit Acquired Hypernatremia Is Not Explained by Sodium Overload or Water Deficit: A Retrospective Cohort Study on Water Balance and Sodium Handling. (14th September 2016) - IJzendoorn, M. C. O. van; Buter, H.; Kingma, W. P.; Navis, G. J.; Boerma, E. C.
Abstract : Background . ICU acquired hypernatremia (IAH, serum sodium concentration (sNa) ≥ 143 mmol/L) is mainly considered iatrogenic, induced by sodium overload and water deficit. Main goal of the current paper was to answer the following questions: Can the development of IAH indeed be explained by sodium intake and water balance? Or can it be explained by renal cation excretion? Methods. Two retrospective studies were conducted: a balance study in 97 ICU patients with and without IAH and a survey on renal cation excretion in 115 patients with IAH. Results. Sodium intake within the first 48 hours of ICU admission was 12.5 [9.3–17.5] g in patients without IAH (n = 50 ) and 15.8 [9–21.9] g in patients with IAH (n = 47 ), p = 0.13 . Fluid balance was 2.3 [1–3.7] L and 2.5 [0.8–4.2] L, respectively, p = 0.77 . Urine cation excretion (urine Na + K) was < sNa in 99 out of 115 patients with IAH. Severity of illness was the only independent variable predicting development of IAH and low cation excretion, respectively. Conclusion . IAH is not explained by sodium intake or fluid balance. Patients with IAH are characterized by low urine cation excretion, despite positive fluid balances. The current paradigm does not seem to explain IAH to the full extent and warrants further studies on sodium handling in ICU patients.